Role of interleukin-2 in wound healing: A review study - Handayani, Putri; Yusuf, Hanifah; Gholib, Gholib (Trends in Infection and Global Health, 2023)
A wound is a condition where tissue damage occurs due to disruption of tissue continuity caused by injury or surgery. Wound healing is a normal biological process in the human body which aims to restore the function and integrity of damaged tissue. In the process, wound healing involves cellular and biochemical responses, including antioxidants and cytokines, which occur locally and systemically. Interleukin-2 (IL-2) is a cytokine that plays a role in wound healing. It is produced by CD8+ and CD4+ T cells in an active state. In the wound healing process, IL-2 plays an important role in activating macrophages and natural killer (NK) cells and encouraging the proliferation of B cells and T cells. In this review, the role of the IL-2 in wound healing is discussed comprehensively.